Progress in plasma research at IPJ and IPPLM, Poland - Sadowski, Marek J.; Skladnik-Sadowska, E.; Scholz, Marek; Wolowski, Jerzy (Вопросы атомной науки и техники, 2006)
The most important results of theoretical and experimental studies of plasmas, which have been achieved at the IPJ in Swierk and IPPLM in Warsaw recently, are presented. Studies of physical phenomena in PF discharges, development of diagnostic techniques and research on new plasma technologies, as performed at IPJ, have been summarized. Studies of dense magnetized plasmas, investigation of physics and applications of laser-produced plasmas; and research on the development of advanced diagnostic techniques for the EURATOM fusion program, as performed at IPPLM, are also described.